2020
DOI: 10.1161/strokeaha.120.031208
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes in Patients With COVID-19 and Acute Ischemic Stroke

Abstract: Recent case-series of small size implied a pathophysiological association between coronavirus disease 2019 (COVID-19) and severe large-vessel acute ischemic stroke. Given that severe strokes are typically associated with poor prognosis and can be very efficiently treated with recanalization techniques, confirmation of this putative association is urgently warranted in a large representative patient cohort to alert stroke clinicians, and inform pre- and in-hospital acute stroke patient pathways. We pooled all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
247
10
23

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 254 publications
(314 citation statements)
references
References 7 publications
(5 reference statements)
27
247
10
23
Order By: Relevance
“…In-hospital mortality in this cohort of COVID-19 patients, which was mainly comprised of cases with ischemic stroke, was higher than recently reported in a cohort of COVID-19 patients with acute ischemic stroke (27.6%). 20 It was also higher than reported 30-day case fatality rates for ischemic stroke, ranging from 9 to 19% 21 or in-hospital mortality of stroke patients admitted to intensive care units, ranging between 14.7 to 21.9%. 22,23 It must be noted that the limited testing in several countries may have led to inflation of death rates.…”
Section: In-hospital Mortalitymentioning
confidence: 71%
“…In-hospital mortality in this cohort of COVID-19 patients, which was mainly comprised of cases with ischemic stroke, was higher than recently reported in a cohort of COVID-19 patients with acute ischemic stroke (27.6%). 20 It was also higher than reported 30-day case fatality rates for ischemic stroke, ranging from 9 to 19% 21 or in-hospital mortality of stroke patients admitted to intensive care units, ranging between 14.7 to 21.9%. 22,23 It must be noted that the limited testing in several countries may have led to inflation of death rates.…”
Section: In-hospital Mortalitymentioning
confidence: 71%
“…Results of another study revealed that patients with COVID-19-related ischemic stroke had worse functional outcome and higher mortality than patients with ischemic stroke and without COVID-19 (48). However, no study has compared the frequency or outcome of neuroimaging findings other than stroke between COVID-19 and non-COVID-19 patients.…”
Section: Association Between Coronavirus Disease 2019 and Abnormal Nementioning
confidence: 99%
“…Howeverthe virus responsible for this illness, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), mayinfluence the presentation of ischaemic stroke 2 , although this conclusion is controversial 3 because of a l a c k o f h i g h quality evidence. In particular, the largest studies havecompared patients with COVID-19-associated stroke with historical controls 4,5 , whose strokes tend to be milder than those seen in contemporaneous controls 6,7 , resulting in a bias towards overestimating the influence of COVID-19 on stroke severity and any other parameters correlated with severity.…”
Section: Introductionmentioning
confidence: 99%
“…Ourobjectives were to determine whether COVID-19 is associated with:a different demographic group; a higher proportion of ischaemic strokes; higher D-dimer values 7 in ischaemic strokes, as may be expec t e d o f a SARS-CoV-2-related hypercoagulable state 8 ; a different distribution of stroke mechanisms, possibly with a predominance of large vessel occlusions 9,10 ; more severe strokes with worse outcomes, including a higher inpatient mortality 4,7 ; a higher rate of early recurrence of stroke; and a delay between the onset of symptoms of infection and of stroke 7 . To address these objectives we analyseddata from a multicentre case-control study of strokes in patients admitted to 13 stroke services in England and Scotland during the 2020 COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%